Pengaruh Kecukupan Modal Dan Likuiditas Terhadap Profitabilitas Pada Bank Umum Syariah - Wulan Riyadi; Dudung Abdullah (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
One of how a bank's financial performance is healthy can be seen through the bank's financial statements. Information regarding the condition of the bank can be used by the bank itself or from outside the bank such as creditors, investors, and customers. The factors that can affect the profitability of Islamic banking are capital adequacy and liquidity. So that Islamic banking, is required to be able to increase profitability every year to attract internal and external parties. This study aims to determine the effect of capital adequacy and liquidity on the profitability of Islamic commercial banks. This research uses descriptive analysis method and verification. The data collection technique used is secondary data. The population in this study are Islamic commercial banks registered in Statistik Perbankan Syariah (SPS). The sampling technique used was purposive sampling with a total sample of 11 Islamic banks with a total of 33 sample data. This research uses classical assumption test analysis, multiple linear regression analysis, coefficient of determination, model feasibility test and hypothesis testing. Based on the results of the study indicate that capital adequacy has a significant effect on profitability and liquidity has no significant effect on profitability